2022
DOI: 10.3390/jpm12050829
|View full text |Cite
|
Sign up to set email alerts
|

A Single Session of Virtual Reality Improved Tiredness, Shortness of Breath, Anxiety, Depression and Well-Being in Hospitalized Individuals with COVID-19: A Randomized Clinical Trial

Abstract: Background: In 2020, the world was surprised by the spread and mass contamination of the new Coronavirus (COVID-19). COVID-19 produces symptoms ranging from a common cold to severe symptoms that can lead to death. Several strategies have been implemented to improve the well-being of patients during their hospitalization, and virtual reality (VR) has been used. However, whether patients hospitalized for COVID-19 can benefit from this intervention remains unclear. Therefore, this study aimed to investigate wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…Groenveld et al [ 41 ] used multimodal VR (physical, cognitive, and relaxation/distraction exercise), and the study by Vlake et al [ 43 ] used COVID-19-related ICU (Intensive Care Unit) stimuli in a virtual environment, which was the only study using an exposure therapy component. The VR intervention time per session was reported to be approximately 10 minutes in four studies [ 42 , 43 , 46 , 47 ]. Additionally, 3-minute-VR was used in one study [ 44 ] and 30-minute-VR in another study [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Groenveld et al [ 41 ] used multimodal VR (physical, cognitive, and relaxation/distraction exercise), and the study by Vlake et al [ 43 ] used COVID-19-related ICU (Intensive Care Unit) stimuli in a virtual environment, which was the only study using an exposure therapy component. The VR intervention time per session was reported to be approximately 10 minutes in four studies [ 42 , 43 , 46 , 47 ]. Additionally, 3-minute-VR was used in one study [ 44 ] and 30-minute-VR in another study [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…44,45 In the former two participant groups (COVID-19 patients and people who underwent strict social distancing), overall, significant improvement was reported in a wide range of psychological distress during COVID-19, ranging from stress, anxiety, depression, and post-traumatic symptoms to quality of life, supporting the efficacy of VR-based psychological intervention. However, in terms of treatment content, the studies that showed clearer effects were eclectic in that social or cognitive exercise, 46,47 or occupational therapy 42 were combined with VR intervention, making it difficult to tease the efficacy of VR apart from other therapeutic modalities. In studies that utilized VR only, 41,43 the beneficial effects were not pronounced or consistent in psychological distress (stress, anxiety, depression, or post-traumatic symptoms) or quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations